MediaLabs in Higher Education: Ecuadorian Experiences - Vivanco, Juan Carlos Maldonado; Franco, María Dolores Guzmán; Hueros, Ana Duarte; Benavides, Andrea Victoria Velásquez (Journal of Posthumanism, 2025)
The present study focuses on the exhaustive analysis of the development and influence of Media Labs in Ecuador, specifically in the field of higher education, in order to discover their impact and effectiveness. Methodology. Based on the collection of numerical and descriptive ideas, the importance of these spaces to improve the quality of creative teaching and incorporate digital tools in the academy is evaluated. For this study, conversations have been held with representatives and leaders of the laboratories (MediaLabs), with the objective of understanding their perspective and competence in the use of technological tools and content within academic environments. Likewise, an exhaustive review of the remains of each group was carried out to evaluate the variety and quality of the resources accessible to educators and students. Results and conclusions. The pedagogical practices of teachers who make use of these resources are examined, as well as their ability to take advantage of digital tools effectively in the classroom.